Ecological Aspects of Coal Mining Enterprises’ Activity in Conditions of Digitalization - Kudryashova Irina; Venger Mihail; Zakharova Natalia (E3S Web of Conferences, 2019)
The study is devoted to the environmental aspects of coal mining enterprises’ activity in digitalization of economy. It substantiates the statement that the innovative development of coal mining enterprises should be based on the concept of greening economy and greening production. The authors proposed modern environmental and economic instruments of state environmental policy. It is substantiated that in order to ensure the effective functioning of coal mining enterprises, it is necessary to apply new digital tools of resource and environmental policies focused on the use of modern software and analytical technologies: optimization packages of applied programs, solving geo-economic problems of visualization of ecological-and-economic state and development of territories. The results of study presented in the paper allow reconciling the complex and controversial tasks of greening enterprises and territories, implementing an adequate local environmental policy, taking into account the human adaptation to harmful natural and man-made factors.